Surface Engineering of All‐Inorganic Perovskite Quantum Dots with Quasi Core−Shell Technique for High‐Performance Photodetectors. Issue 11 (17th April 2020) - Saleem, Muhammad Imran; Yang, Shengyi; Zhi, Ruonan; Sulaman, Muhammad; Chandrasekar, Perumal Veeramalai; Jiang, Yurong; Tang, Yi; Batool, Attia; Zou, Bingsuo
Abstract: All‐inorganic lead halide perovskites with good surface morphology show substantial prospect for optoelectronic devices. However, the anion exchange of coordinated alkylamine ligands (e.g., oleic acid and oleylamine) can detach ligands and induce more interface trap sites, subsequently to reduce device performance. In this paper, therefore, a simple solution‐processed route is presented to synthesize quasi coreshell CsPbBr3 formamidinium iodide (FAI = CH(NH2 )2 I) colloidal quantum dots (CQDs), and then it is applied as the active layer for photodetectors by finely controlling the ligands exchange. The presence of FAI = CH(NH2 )2 I on CsPbBr3 is confirmed by Fourier transform infrared spectroscopy. As a result, the photodetector ITO/ZnO (100 nm)/CsPbBr3 (150 nm)/Au show an enhanced specific detectivity over 10 13 Jones with a responsivity of 19 A W 1 under 3 mW cm 2 405 nm illumination at 1.5 V. The experimental data show that the enhanced device performance is due to the improved crystallinity and less surface defects of CsPbBr3 CQDs, as the result of less alkylamine ligands is detached during its FAI passivation, thus the charge carriers' mobility of the film is improved. Therefore, it provides a promising way for high‐performance solution‐processed all‐inorganic CsPbBr3 based optoelectronic devices. Abstract : The formation of quasi core−shell CsPbBr3 −formamidinium iodide (FAI = CH(NH2 )2 I) colloidal quantum dots (CQDs) can passivate the surface efficiently, and it provides a promising way for high‐performance solution‐processed all‐inorganic CsPbBr3 photodetectors.